Pemidanaan dan Strategi Kepolisian dalam Mencegah Penyebaran Narkotika - Hellyn Kristiono; Nynda Fatmawati (KRTHA BHAYANGKARA, 2023)
This study aims to determine criminal sanctions against perpetrators of narcotics crimes, strategies that can be carried out by the police to reduce drug trafficking and obstacles to law enforcement officers in eradicating narcotics cases. The data analysis method used in this study is analytical descriptive with a normative juridical approach. The results of the study stated that criminal sanctions are regulated in Law No. 35 of 2009 concerning Narcotics, regarding criminal provisions regulated in Articles 111 to Article 147, while the strategy carried out by the police in eradicating the spread of narcotics is through pre-emptive, preventive and repressive efforts. Pre-emptive efforts are carried out by coaching the community through outreach about the effects of narcotics, preventive efforts are carried out by increasing supervision of narcotics trafficking and repressive efforts are also carried out as prosecution of drug crime acts. Obstacles to law enforcement officers in disclosing narcotics cases are divided into two, namely internal obstacles and external obstacles.